IMPLEMENTATION OF THE SAW METHOD IN THE SCHOLARSHIP DECISION SUPPORT SYSTEM - Faulinda Ely Nastiti; Ardian Pamungkas; Sopingi - Sopingi (STMIK Royal, 2022)
Abstract: The number of applicants for scholarship recipients is many, so in the registration process, the scholarship provider provides several requirements that students must meet, and these requirements have criteria with different weight values. The number of applicants for the scholarship recipients is enormous; a Decision Support System (DSS) is needed to help the selection process be more accessible and faster and reduce errors in determining scholarship recipients. The data collection method uses interviews, observations, and literature with the waterfall's system development method. The calculation of the criteria used in developing this system is the Simple Additive Weighting (SAW) method. Comparing the final results between manual and system analyses shows that the equation is close to 100%. Still, the final results may be different because manual calculations use raw values, while system calculations use the Simple Additive Weighting (SAW) method, which compares alternatives.. Keywords: decision support system; scholarship; simple additive weighting Abstrak: Pendaftar calon penerima beasiswa tidak sedikit jumlahnya, sehingga pada proses pendaftaran pihak pemberi beasiswa memberikan sejumlah persyaratan yang harus dipenuhi oleh siswa, dan persyaratan tersebut memiliki kriteria dengan nilai bobot yang berbeda-beda. Jumlah siswa yang mengajukan beasiswa sangat banyak, dan memerlukan sistem pendukung keputusan untuk mempermudah dan mempercepat proses seleksi serta mengurangi kesalahan dalam menentukan penerima beasiswa. Metode dalam mengumpulkan data menggunakan metode wawancara, observasi, dan literatur dengan metode pengembangan sistem menggunakan waterfall. perhitungan kriteria yang digunakan dalam pengembangan sistem ini adalah metode SAW (Simple Additive Weighting). Perbandingan hasil akhir antara perhitungan manual dan sistem menunjukkan persamaan mendekati 100%, namun hasil akhir bisa saja berbeda karena perhitungan manual menggunakan nilai mentah, sedangkan perhitungan sistem menggunakan metode SAW (Simple Additive Weighting) yang perhitungan dengan cara membandingkan alternatif. Kata kunci: beasiswa; simple additive weighting; sistem pendukung keputusan